2011
DOI: 10.1161/circresaha.111.255067
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 3 Regulates Smooth Muscle Differentiation in Neural Crest Cells and Development of the Cardiac Outflow Tract

Abstract: Rationale The development of the cardiac outflow tract (OFT) and great vessels is a complex process that involves coordinated regulation of multiple progenitor cell populations. Among these populations, neural crest cells make important contributions to OFT formation and aortic arch remodeling. While numerous signaling pathways, including Notch, have been implicated in this process, the role of epigenetics in OFT development remains largely unexplored. Objective As histone deacetylases (Hdacs) play important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 44 publications
0
49
1
Order By: Relevance
“…Hdac3 in NCCs is required to regulate PAA and OFT development; however, its direct target genes are unknown (38). Some histone-modifying enzymes are also known to regulate OFT development, but their cellular sites of actions are undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Hdac3 in NCCs is required to regulate PAA and OFT development; however, its direct target genes are unknown (38). Some histone-modifying enzymes are also known to regulate OFT development, but their cellular sites of actions are undefined.…”
Section: Discussionmentioning
confidence: 99%
“…1G). Previously, we demonstrated that neural crest-specific genetic deletion of HDAC3 resulted in anomalous outflow tract septation and distal outflow tract mor- phogenesis; however, outflow tract rotation and semilunar valve development were unaffected (69). Instead, second heart field-derived myocardium at the base of the outflow tract governs the normal outflow tract rotation (70).…”
Section: Myh6komentioning
confidence: 99%
“…For example, Hdac3, a member of the Class I HDAC family, has been implicated in cardiac development and homeostasis (Montgomery et al, 2008;Singh et al, 2011), acting by repressing the expression of Tbx5 in early development (Lewandowski et al, 2014). During development, it is highly expressed in the SAN (Wu et al, 2014), AVN and Purkinje fibres (Risebro et al, 2012).…”
Section: Histone Modifications Mediating Ccs-specific Gene Expressionmentioning
confidence: 99%